2004
DOI: 10.1126/science.1095455
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Word Meaning and World Knowledge in Language Comprehension

Abstract: Although the sentences that we hear or read have meaning, this does not necessarily mean that they are also true. Relatively little is known about the critical brain structures for, and the relative time course of, establishing the meaning and truth of linguistic expressions. We present electroencephalogram data that show the rapid parallel integration of both semantic and world knowledge during the interpretation of a sentence. Data from functional magnetic resonance imaging revealed that the left inferior pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

87
825
14
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 995 publications
(966 citation statements)
references
References 17 publications
87
825
14
8
Order By: Relevance
“…In other words they violated so-called 'world knowledge' about typical human actions in ecological environments. For this reasons we expected the congruent/incongruent contrast to elicit a N400 similar to the one discovered by Hagoort et al [4] for linguistically mediated pragmatic knowledge. As for earlier ERP components, we did not have specific expectations since, to our knowledge; incongruent human actions vs. congruent human actions were never previously compared in ERP investigations.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…In other words they violated so-called 'world knowledge' about typical human actions in ecological environments. For this reasons we expected the congruent/incongruent contrast to elicit a N400 similar to the one discovered by Hagoort et al [4] for linguistically mediated pragmatic knowledge. As for earlier ERP components, we did not have specific expectations since, to our knowledge; incongruent human actions vs. congruent human actions were never previously compared in ERP investigations.…”
supporting
confidence: 56%
“…The study of N400 behaviour has helped us to understand how meanings are accessed, stored and integrated in the lexical semantic system. It has also been demonstrated that N400 is sensitive not only to word meanings but also to violations of world knowledge learned during everyday life [4] or to semantic violations in deaf native signers [23].However, to our knowledge, the observation of linguistic components has not been applied so far to the study of gesture coding, for which it is known that there are permanent representational units in the inferior parietal and inferior frontal cortex. Indeed, apart from communicative gestures such as sign language (e.g., ASl or BSL), goal-directed gestures whose intent is not communicative are also recognized as unitary meaningful units by premotor and somatosensory mirror neurons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both experiments yielded N400 effects that are interpreted to reflect postlexical integration processes, in particular the difficulty of integrating sentence-final words into the preceding context (Friederici, 2002;Hagoort, Hald, Bastiaansen, and Petersson, 2004;Kutas, and Van Petten, 1994). The different magnitude of the N400 between semantic and phonological errors in Experiment 2 suggests an additional difference in lexical processing (Besson et al, 1992;Praamstra et al, 1994;Radeau et al, 1995Radeau et al, , 1998Rugg, 1990;Van Petten, and Luka, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research in psycholinguistics and cognitive neuroscience has shown that the amplitude of this ERP component is directly influenced by inconsistencies of local and contextual information (e.g. Hagoort, Hald, Bastiaansen, & Petersson, 2004;Van Berkum, Zwitserlood, Hagoort, & Brown, 2003), as well as the degree of plausibility for the overall message (DeLong, Quante, & Kutas, 2014). For example, typical N400 responses to local semantic anomalies (e.g.…”
mentioning
confidence: 99%